Opportunities in valorisation of industrial food waste into extruded snack products – A review - RALENG, ANGAM; SINGH, N G JOYKUMAR; CHAVAN, PRASAD; ATTKAN, ARUN KUMAR (The Indian Journal of Agricultural Sciences, 2022)
Fruit and vegetable by-product production produces a large amount of waste material, which poses a significantdisposal issue for the food industry and can have harmful effect on the environment, if left unused. This waste includes nutrients like dietary fibre, vitamins and minerals, as well as bioactive like flavonoids and lycopene. The functional and nutritional characteristics of by-products of fruit and vegetable processing, as well as their possible utilization in food extrusion technology as noble ingredients for enhancing the nutritional value in snack foods are the subject of this study. This review also proposes a method for producing a less expensive value-added ingredient, which reduces the current methods of disposing of these waste (that can have a negative impact on the environment) but still saving money for the manufacturer. The potential and opportunity for fruit and vegetable by-products incorporation in extruded snack products, thereby enriching the fibre and other nutritional components of the snack, is reflected in this paper. Ingredient industries are constantly searching for cheaper but value-added raw materials. So, this review will also enhance the horizon for not only the food industries but also encourage micro food entrepreneurs, the Self Help Groups and certain other domestic food enterprises in terms of the utility of the food waste, the methods of development and value added aspects as a whole.